Pengaruh Ukuran Perusahaan dan Leverage Terhadap Audit Delay Pada Perusahaan Sub Sektor Perhotelan, Pariwisata & Restaurant yang Terdaftar di Bursa Efek Indonesia - Ika Supratiwi; Maftukhin; Nasiruddin; Hilda Kumala Wulandari; Amelia Sholeha (Universitas Muhadi Setiabudi, 2021)
Audit delay plays an important role in publishing financial statement information. In this study, the author proves whether company size and leverage affect audit delays by including empirical evidence. The data processed is secondary data by analyzing financial statements covering the hospitality, tourism and restaurant sub-sectors that have been listed on the Indonesia Stock Exchange 2015-2019. The type of method used by the sample for this study was determined using targeted sampling techniques and out of a total of 36 companies there were 30 companies selected to be used as research samples Data processing analysis methods using SPSS 22 software. The results of this study that the size of the company and leverage showed the results had a positive effect on audit delay.